Meningkatkan Kepedulian Anak Terhadap Lingkungan Sejak Dini pada Panti Asuhan Karya Betzy Indonesia - Nicolas Septian Siahaan; Erni Asneli Asbi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
A clean and healthy environment is an environment free of various impurities, including dust, garbage and odors. The process of disease transmission is caused by microbes, a clean and healthy environment also means that it must be free from viruses, pathogenic bacteria and various disease sectors. Many human activities have a negative impact on environmental quality, for example poor management of waste and waste, increased use of materials that cannot be degraded by nature. Low public awareness of environmental hygiene and health also affects and exacerbates environmental conditions. There are still many people who throw garbage in rivers or ditches which can cause rivers to overflow and floods. Seeing this case, the practitioner took the initiative to provide material and practice with the aim of increasing children's awareness of the environment from an early age. Through this Field Work Practice, the practitioner aims to make the orphans more sensitive and pay more attention to their surroundings. In this Field Work Practice 2 the focus is on groups, with the aim that a group experiences a change for the better.